Math, asked by aayushgautam226, 6 months ago

find HCF of ab^2+a^3,2ab^2-4a^2b-6a^3 and 2a(ab+a^2)^2​

Answers

Answered by ibrahimarmankhan
0

Answer:

Answer:

2ab-3

Step-by-step explanation:

\begin{gathered}4a^{2}b^{3} -9b= b(2ab-3)(2ab+3)\\2a^{2}b^{2} -ab -3=(ab+1)(2ab-3)\\Thus, HCF= 2ab-3\end{gathered}

4a

2

b

3

−9b=b(2ab−3)(2ab+3)

2a

2

b

2

−ab−3=(ab+1)(2ab−3)

Thus,HCF=2ab−3

Answered by hkishor60gmailcom
1

HCF of ab²+a³,2ab²-4a²b-6a³ = a

please mark me as brainlist

Similar questions